2001
DOI: 10.1002/jmri.10017
|View full text |Cite
|
Sign up to set email alerts
|

Proton MR spectroscopy of the lumbar spine in patients with glycogen storage disease type Ib

Abstract: Glycogen storage disease type Ib is an autosomal recessive inherited metabolic disorder resulting from deficiency of the microsomal glucose-6-phosphatase enzyme system. Six patients (three of which were treated with granulocyte colony stimulating factor) suffering from this disease were examined using image guided localized proton magnetic resonance (MR) spectroscopy. The relative signal intensities of water and lipid protons of the lumbar spine were determined. Comparison was made with iliac crest biopsies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Recently, a number of works have been devoted to age‐, sex‐, and composition‐differences of bone marrow specified by magnetic resonance spectroscopy (MRS) in healthy subjects (12, 13) as well as to comparison of normal and pathological bone marrow (14–17). It has been shown that the W/F ratio in healthy vertebral bone marrow varies from 9.0 (11–20 years old) to 0.1 (>60 years old) (12–16). For subjects between 30–60 years old W/F ranges within 2–0.5.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of works have been devoted to age‐, sex‐, and composition‐differences of bone marrow specified by magnetic resonance spectroscopy (MRS) in healthy subjects (12, 13) as well as to comparison of normal and pathological bone marrow (14–17). It has been shown that the W/F ratio in healthy vertebral bone marrow varies from 9.0 (11–20 years old) to 0.1 (>60 years old) (12–16). For subjects between 30–60 years old W/F ranges within 2–0.5.…”
Section: Discussionmentioning
confidence: 99%
“…Spectra were manually phase-corrected. The expected resonances of the lipid peaks (Table 1) were determined from published human BM spectra (28)(29)(30)(31). Soft constraints of 6 0.05 ppm were imposed around the resonances to allow some flexibility to the fitting algorithm.…”
Section: Mr Spectroscopymentioning
confidence: 99%
“…The cellularity of bone marrow can be calculated from the most dominant peaks in the proton spectrum of marrow from methylene and water peaks (14). Proton MRS showed a good correlation between the cellularity and water signal intensity compared to bone marrow biopsy (14,40,41). These studies suggest that MRS can be used to evaluate the bone marrow cellularity or biochemical composition in vivo in different disease entities.…”
Section: Discussionmentioning
confidence: 82%